English acculturation in food and coffee shop naming: Examining its impact on local languages - Zurriyati Zurriyati; Fadhlur Rahman; Ella Yuzar; Alemina Br. Perangin-angin (Studies in English Language and Education, 2025)
The proliferation of the English language has resulted in the blending of the English language and culture into the national and indigenous languages of emerging countries, including Indonesia. Although most people in North Aceh, Indonesia, are Acehnese, some restaurants and coffee shops are named in English. This study explores how English acculturation in the naming of food and coffee shops affects the visibility and preservation of local languages in this area. Using Berrys acculturation framework, the research categorizes naming practices into assimilation, integration, and isolation, analyzing how English, Indonesian, and Acehnese elements are blended or separated in commercial branding. Data were gathered through interviews with business owners and customers, as well as observations of shop names and menus. The findings reveal that assimilation is the most dominant strategy, reflecting a preference for English-language branding as a symbol of modernity and prestige, particularly among younger entrepreneurs. However, some businesses still adopt integrated or local naming conventions to retain cultural identity. These practices have sociolinguistic implications, as the increased dominance of English may marginalize the Acehnese language in public spaces. The study calls for culturally responsive language planning to ensure a balance between global appeal and local heritage in commercial language use.